Changes in the Leptin to Adiponectin Ratio Are Proportional to Weight Loss After Meal Replacement in Adults With Severe Obesity - Rafey, Mohammed Faraz; Abdalgwad, Razk; O'Shea, Paula Mary; Foy, Siobhan; Claffey, Brid; Davenport, Colin; O'Keeffe, Derek Timothy; Finucane, Francis Martin (Frontiers in Nutrition, 2022)
Hypocaloric diets are known to induce changes in adipokine secretion, but the influence of a low energy liquid diet (LELD) on the leptin: adiponectin ratio (LAR), a measure of insulin resistance and cardiovascular risk, has not previously been investigated in patients with severe obesity. We conducted a prospective, single-centre cohort study of adults with severe obesity (defined as body mass index (BMI) ≥40 kgm-2, or ≥35 kgm-2 with co-morbidities) who completed a 24-week milk-based LELD. We measured leptin, adiponectin and LAR at the start and on completion of the programme. Of 120 patients who started, 52 (43.3 %) completed the programme. Their mean age was 50.3±11.2 (range 18-74) years, 29 (55.8 %) were female and 20 (38.5 %) had type 2 diabetes mellitus (T2DM). Weight decreased from 148.2±39.6 to 125.4±34.8 kg and BMI decreased from 52.4±11.1 to 44.3±9.8 kgm-2, respectively (all p<0.001). In patients with T2DM, HbA1c decreased from 60.0±17.4 to 47.5±15.5 mmol/mol (p<0.001). Leptin decreased (from 87.2 [48.6, 132.7] to 39.1 [21.0, 76.4] ng/ml) and adiponectin increased (from 5.6 [4.5, 7.5] to 7.1 [5.5, 8.5] µg/ml), with a reduction in LAR from 15 [8.4, 22.4] to 5.7 [3.0, 9.1] ng/µg (all p<0.001), indicating decreased insulin resistance. The percentage weight lost was associated with the percentage reduction in LAR (ß=2.9 [1.7, 4.1], p<0.001) and this association was stronger in patients with T2DM. Patients with severe obesity who completed a milk-based LELD had a substantial reduction in LAR, consistent with decreased insulin resistance and cardiovascular risk, proportional to weight loss.